THE IMPACT OF CONSUMERISM TOWARD REBECCA'S PERSONALITY IN P. J. HOGAN'S CONFESSIONS OF A SHOPAHOLIC MOVIE (2009):A PSYCHOANALYTIC APPROACH - NOVIANI, ANGGARI KHARISMA (2011)
The research is proposed to analyze the impact of Rebecca's personality toward consumerism with Psychoanalytic Approach. There are two objectives: the first is to analyze the impact of consumerism toward Rebecca's personality in Confessions of a Shopaholic based on psychoanalytic approach, and the second is to analyze P. J. Hogan's Confessions of a Shopaholic movie based on the structural elements of movie. This study is a descriptive qualitative study, using the movie of Hogan's Confessions of a Shopaholic. And Confessions of a Shopaholic's major character as the object of analysis of the study. There are two kinds of data sources used in this analysis, namely primary and the secondary. The primary data sources are the play and script of the play itself and the secondary data sources are some books, internet and articles related to the subject. The technique of data collection in this research is watching the original movie for several times; reading the movie script; determining the character that will be analyzed; taking notes of important thing both of primary and secondary data sources; classifying and determining the relevant data and; notes the material and other resources that related into the movie and the analysis. In analyzing the data, the researcher employs descriptive qualitative analysis. For the last, the researcher makes an analysis of Rebecca's id, ego, and superego. The researcher uses the theory of Psychoanalytic by Sigmun Freud because it is relevant to the problem. Based on the analysis, the outcome of this study shows that Rebecca's character described as shopaholic, fashionable and stylish, extravagant, imaginative, dishonest, desperate, careless, panicky, curious and a brandname follower. The impact of consumerism toward the main character can be divided into shopaholic, wasteful life and being snared of debt and being oppressed in her life. Rebecca immediately got bankrupt, she is debtor, and she is fired from her job.